2012
DOI: 10.1038/bjc.2012.190
|View full text |Cite
|
Sign up to set email alerts
|

The risk of pancreatic cancer in symptomatic patients in primary care: a large case–control study using electronic records

Abstract: Background:Over 8000 new pancreatic cancers are diagnosed annually in the UK; most at an advanced stage, with only 3% 5-year survival. We aimed to identify and quantify the risk of pancreatic cancer for features in primary care.Methods:A case–control study using electronic primary care records identified and quantified the features of pancreatic cancer. Cases, aged ⩾40 in the General Practice Research Database, UK, with primary pancreatic cancer were matched with controls on age, sex and practice. Putative fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(134 citation statements)
references
References 24 publications
6
127
1
Order By: Relevance
“…Testing for association used univariable and multivariable conditional logistic regression, performed in three stages. [17][18][19][20] The variable for hypergammaglobulinaemia was not included in the multivariable analyses as it could be considered an outcome variable rather than an explanatory variable. The first stage, univariable analysis, used a P-value threshold of 0.1 or below to identify candidate variables for multivariable analysis.…”
Section: Analysis and Statistical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Testing for association used univariable and multivariable conditional logistic regression, performed in three stages. [17][18][19][20] The variable for hypergammaglobulinaemia was not included in the multivariable analyses as it could be considered an outcome variable rather than an explanatory variable. The first stage, univariable analysis, used a P-value threshold of 0.1 or below to identify candidate variables for multivariable analysis.…”
Section: Analysis and Statistical Methodsmentioning
confidence: 99%
“…19,20,[22][23][24] This study, the largest reported, provided ample power to identify rare but potentially clinically relevant symptoms of myeloma, and allowed sub-analyses by age. The results are highly likely to be generalisable.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The GPRD applies stringent data quality levels on their practices. 14,15 Cases and controls Cases had a record of one of 22 GPRD kidney cancer codes (based on Read Codes and linked to ICD-10 classifications; available from authors) between January 2000 and December 2009 inclusive. All were aged ≥40 years with a minimum of 1 year of data before diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…5 An association between diabetes and uterine cancer has been reported before and with a similar strength to the association with a raised glucose found in the present study. 24 Finally, a raised platelet count has been reported in primary care studies of lung, and pancreatic cancer, 25,26 as well as secondary care studies of ovarian cancer.…”
Section: Comparison With Existing Literaturementioning
confidence: 97%